The association between indices of obesity and common clinical measures in adults with and without type 2 diabetes - Nayak, Shivananda B.; Gosine, Chandani; Ramkissoon, Shazana; Baig, Andria; Kamalodeen, Aisha; Dave, Mohan; Mohammed, Reshad; Poolchan, Suren; Harripersad, Alex; Singh, Shamjeet (International Journal of Research in Medical Sciences, 2017)
Background: The aim of this study was to determine the differences amongst the anthropometric measurements, lipid profile, blood pressure and body shape in diabetics as well as non-diabetics. Methods: This was a cross-sectional study comprised of 309 subjects with 91 males and 218 females. Of this, there were 217 diabetics and 92 non-diabetics. The sample was taken from three hospitals in Trinidad. Lipid profile and blood pressure were taken from each facility’s physician’s notes while anthropometric measurements were taken from the patients themselves. Results: The diabetic group had elevated body mass index and waist to hip ratios were significant (P <0.05) when compared to non-diabetics. There was no significant association of lipid profile, blood pressure, waist circumference and waist to height ratios between diabetics and non-diabetics. As age increased, the prevalence of type 2 diabetes mellitus was more common. Out of 217 diabetics, 173 were of East Indian descent. With regards to gender, more males were found to be diabetics resulting from having an android body shape as compared to females (gynoid body shape). Conclusion: It was found that of all the anthropometric measurements used, waist to hip ratio was found to be the most effective indicator of type 2 diabetes mellitus in Trinidadians, while body mass index was found to be the least effective indicator.